Designing and validating a podcast-assisted project-based learning procedure for EFL speaking development - Rafi’ah Nur; Mutmainna Muinuddin M Dyah; Ammang Latifa; Amaluddin Amaluddin; Areski Wahid; Rusdiana Junaid (Universitas Syiah Kuala, 2026)
This study designed, validated, and refined a podcast-assisted Project-Based Learning (PjBL) instructional procedure for EFL speaking development in an Indonesian higher-education context. Framed as model development within a descriptive–exploratory educational design research/design-and-development research approach, the study produced an initial prototype specifying learning activities and sequencing, then subjected the procedure to expert review and iterative refinement. Two expert validators evaluated the model using a 5-point validation rubric comprising 16 indicators covering key instructional components (Introduction, Core, Closing, and Assessment) and four criteria (logicality, appropriateness, alignment, and non-controversiality), complemented by open-ended comments to guide revisions. Quantitative ratings were analyzed using the Content Validity Index (CVI) and Aiken’s V, supported by descriptive summaries and agreement metrics. Findings indicate excellent content validity: all indicators met the relevance criterion (I-CVI = 1.00; S-CVI/Ave = 1.00; S-CVI/UA = 1.00). Aiken’s V coefficients ranged from 0.75 to 1.00, with a mean of 0.898 (≈0.90), and the overall feasibility/appropriateness rating was high (M = 4.59/5). Feedback from, the validators informed targeted refinements, particularly strengthening the production-oriented Core phase by clarifying scaffolding and integrating an explicit feedback–revision cycle, including an individual (solo) podcast recording task. The final model organizes instruction into three connected phases (Introduction–Core–End) with assessment embedded across phases, offering a validated, classroom-ready procedure for integrating authentic audio input and project-based speaking production. The findings have important implications for teachers who wish to explore alternative ways to teach language using digital and project-based methods.